Preclinical evaluation of peptide-based radiotracers for integrin αvβ6-positive pancreatic carcinoma = Präklinische Evaluation von Peptid-basierten Radiotracern für Integrin αvβ6-positive Pankreaskarzinome - Müller, Martin; Altmann, Annette; Sauter, Max; Lindner, Thomas; Jäger, Dirk; Rathke, Hendrik; Herold-Mende, Christel; Marmé, Frederik; Babich, John; Mier, Walter; Haberkorn, Uwe (Nuklearmedizin, 2019)
Introduction: Integrin αvβ6 shows a high expression rate in several cancer entities. As it is absent in most healthy adult tissues, it represents a promising target for tumor targeting with peptidic radiotracers. This study was performed to pave the way of the recently published αvβ6-binding peptide SFLAP3 for the clinical application in patients with pancreatic cancer. Methods: The expression of integrin αvβ6 on several pancreatic cancer cell lines was assessed using flow cytometry and cell binding assays. The affinity was determined in competition binding assays followed by internalization and efflux studies. To increase the affinity, the binding sequence was modified and trimerization of the SFLAP3 peptide was achieved by oxime ligation. PET and biodistribution assays were conducted in Capan-2 tumor bearing mice. Finally, a first pancreatic tumor patient was examined with 68 Ga-DOTA-SFLAP3. Results: Flow cytometric analysis and in vitro cell binding revealed high expression of integrin αvβ6 on most pancreatic tumor cell lines. Modification of SFLAP3 led to compounds with improved in vitro binding properties. Unfortunately, these superior properties could not be transferred into improved pharmacokinetics. Consequently, the first pancreatic tumor patient was examined with 68 Ga-DOTA-SFLAP3. The PET revealed specific accumulation (with SUV (max) values in the metastases ranging from 5 to 10) and a long retention in the tumor. Conclusion: SFLAP3 showed high affinity to integrin αvβ6 on pancreatic cancer cell lines. The in vitro performance could be confirmed in tumor bearing mice and by PET imaging. These data suggest that DOTA-SFLAP3 is a promising tracer for targeting αvβ6-expressing pancreatic tumors.